Differential Response of the Components of Functional Diversity in Orestias Fishes (Cyprinodontidae) of the High Andean Plateau - Castro-Morales, S; Rojas-Figueroa, P (Elsevier B.V., 2024)
Orestias (Cyprinodontiformes, Cyprinodontidae) is a diverse genus of freshwater fish endemic to the high Andean plateau (Altiplano) of the Andes Mountains, South America. Within the Altiplano, Orestias species form assemblages of varying taxonomic richness, exhibiting considerable diversity in morphological forms and sizes, and occupying different habitat types. Here, we investigate the functional diversity of Orestias assemblages in two basins within the Altiplano: Titicaca Lake and the southwestern Altiplano basins. Titicaca Lake is characterized by high species diversity that evolved sympatrically, while the southwestern Altiplano has lower species diversity that evolved allopatrically. Given that taxonomic diversity under sympatric conditions can promote greater functional diversity, we hypothesize that the Titicaca assemblage should display higher indicators of functional diversity. By using traits related to locomotion, food acquisition, and habitat type to quantify functional diversity we used four functional diversity indicators (functional richness, divergence, specialization, and originality) to compare the Orestias assemblages in two basins. We found no difference in functional divergence and originality between the Orestias from two basins. However, functional specialization was higher in the southwestern Altiplano, contrary to our hypothesis. Only functional richness was higher Titicaca assemblage; supporting our hypothesis. The differentiation between assemblages arises primarily from traits associated with locomotion and food acquisition. Several Orestias species are considered endangered and the extinction of any these taxa could impact the functional diversity of these basins. © 2024 The Authors